Ultrasonographic Evaluation of Chronic Pancreatitis with ERCP Correlation (BIRDEM Medical Journal, 2016)
Objective: This study was performed to assess the diagnostic accuracy of transabdominal ultrasonography in suspected patients of chronic pancreatitis correlating with ERCP.Materials and methods: This cross-sectional study was performed on patients with chronic pancreatitis in the department of radiology and imaging, in collaboration with department of Gastroenterology of BSMMU and BIRDEM from 1st June 2008 to 31st may 2009. Total 60 consecutive patients of different age groups referred for USG of upper abdomen with a suspicion of chronic pancreatitis. At first all the patients were evaluated by detail history and clinical examination. USG of pancreas was performed in all cases. Then all patients underwent ERCP in the Gastroenterology department. The ERCP reports were collected and correlated with USG findings. Among all patients 4 refused to do ERCP and 6 patients had ERCP cannulation failure. Finally, 50 patients were considered as study sample.Results:Sonographically abnormalities were detected in 43 (86%) cases; 1 of them was diagnosed as normal by ERCP. Out of 7 (14%) sonographically normal, 3 were proved normal by ERCP and 4 cases, which were missed by sonography, were diagnosed as chronic pancreatitis by ERCP. Sensitivity of ultrasonography in diagnosing chronic pancreatitis was 91.3% and specificity was 75%, positive predictive value was 97.7%, negative predictive value was 42.9% and accuracy was 90%.Conclusion: Ultrasonography has significant sensitivity, specificity, positive predictive value and accuracy in the diagnosis of chronic pancreatitis and we consider ultrasonography as an appropriate imaging tool for diagnosis of chronic pancreatitis.Birdem Med J 2015; 5(1): 5-8